Targeting Histone Deacetylases in Myeloid Cells Inhibits Their Maturation and Inflammatory Function With Limited Effects on Atherosclerosis - Luque-Martin, Rosario; Van den Bossche, Jan; Furze, Rebecca C.; Neele, Annette E.; van der Velden, Saskia; Gijbels, Marion J.J.; van Roomen, Cindy P.P.A.; Bernard, Sharon G.; de Jonge, Wouter J.; Rioja, Inmaculada; Prinjha, Rab K.; Lewis, Huw D.; et al. (Frontiers in Pharmacology, 2019)
Monocytes and macrophages are key drivers in the pathogenesis of inflammatory diseases. Epigenetic targets have been shown to control the transcriptional profile and phenotype of these cells. Since histone deacetylase protein inhibitors (iHDAC) demonstrate profound anti-inflammatory activity, we wanted to test whether HDAC inhibition within monocytes and macrophages could be applied to suppress inflammation in vivo. ESM technology incorporates an esterase-sensitive motif (ESM) to small molecules to allow targeting of cells that express carboxylesterase 1 (CES1), such as mononuclear myeloid cells. In this study we utilised an HDAC inhibitor modified with the ESM-technology (ESM-iHDAC) to target monocytes and macrophages in mice in both an acute response model and an atherosclerosis model. We demonstrate that the molecule blocks the maturation of peritoneal macrophages and inhibits pro-inflammatory cytokine production in both models but to a lesser extent in the atherosclerosis model. Despite regulating the inflammatory response, ESM-iHDAC did not significantly affect plaque size or phenotype, although histological classification of the plaques demonstrated a significant shift to a less severe phenotypes. We hereby show that HDAC inhibition in myeloid cells impairs the maturation and activation of peritoneal macrophages but only shows limited efficacy in a model of atherosclerosis.